What Happens Next? : Matters of Life and Death - Bauer, Douglas (Book collections on Project MUSE., 2013)
What is life about but the continuous posing of the questions: what happens next, and what do we make of it when it arrives? In these highly evocative personal essays, Douglas Bauer weaves together the stories of his own and his parents' lives, the meals they ate, the work and rewards and regrets that defined them, and the inevitable betrayal by their bodies as they aged. His collection features at its center a long and memory-rich piece seasoned with sensory descriptions of the midday dinners his mother cooked for her farmer husband and father-in-law every noon for man.